Pilot Project Program Duta Diabetes: Upaya Pencegahan Penyakit Diabetes Tipe 2 di Provinsi Riau, Fase Rekruitmen - Nila Kusumawati; Abdul Hamid; Salsabilla Adilia Anwar; Endang Suswati (Abdimas Universal, 2024)
The Diabetes Ambassador Program is a program initiated by the Indonesian Diabetes Center at Pahlawan Tuanku Tambusai University as an effort to prevent and treat diabetes in society. This program aims to help villages that experience a shortage of health human resources. The Diabetes Ambassador Program is carried out by recruiting and preparing village teenagers to become an extension of the community health center in preventing diabetes in the village. The Diabetes Ambassador Program pilot project was carried out in Pantai Cermin Village, Tapung District, Kampar Regency, Riau Province, which is recorded as one of the villages that contributes the most to diabetes in Kampar Regency, Riau Province. The Pilot project for the Diabetes Ambassador Program begins with a recruitment stage where village teenagers who are interested in becoming diabetes ambassadors take part in a selection process to be appointed as diabetes ambassadors.